[RhIII(dmbpy)2Cl2]+ as a Highly Efficient Catalyst for Visible‐Light‐Driven Hydrogen Production in Pure Water: Comparison with Other Rhodium Catalysts1. Issue 2 (21st November 2012) - Stoll, Thibaut; Gennari, Marcello; Serrano, Isabel; Fortage, Jérôme; Chauvin, Jérôme; Odobel, Fabrice; Rebarz, Mateusz; Poizat, Olivier; Sliwa, Michel; Deronzier, Alain; Collomb, Marie‐Noëlle
Abstract We report a very efficient homogeneous system for the visible‐light‐driven hydrogen production in pure aqueous solution at room temperature. This comprises [RhIII(dmbpy)2Cl2]Cl (1) as catalyst, [Ru(bpy)3]Cl2 (PS1) as photosensitizer, and ascorbate as sacrificial electron donor. Comparative studies in aqueous solutions also performed with other known rhodium catalysts, or with an iridium photosensitizer, show that 1) the PS1/1/ascorbate/ascorbic acid system is by far the most active rhodium‐based homogeneous photocatalytic system for hydrogen production in a purely aqueous medium when compared to the previously reported rhodium catalysts, Na3[RhI(dpm)3Cl] and [RhIII(bpy)Cp*(H2O)]SO4 and 2) the system is less efficient when [IrIII(ppy)2(bpy)]Cl (PS2) is used as photosensitizer. Because catalyst 1 is the most efficient rhodium‐based H2‐evolving catalyst in water, the performance limits of this complex were further investigated by varying the PS1/1 ratio at pH 4.0. Under optimal conditions, the system gives up to 1010 turnovers versus the catalyst with an initial turnover frequency as high as 857 TON h−1. Nanosecond transient absorption spectroscopy measurements show that the initial step of the photocatalytic H2‐evolution mechanism is a reductive quenching of the PS1 excited state by ascorbate, leading to the reduced form of PS1, which is then able to reduce [RhIII(dmbpy)2Cl2]+ to [RhI(dmbpy)2]+. This reduced species can react with protons to yield the hydride [RhIII(H)(dmbpy)2(H2O)]2+, which is the key intermediate for the H2 production.